Organizational Commitment Bridges Job Satisfaction and Organizational Citizenship Behavior in Hotel Employees - Mohyi, Achmad (Research Horizon, 2026)
Employee behavior beyond formal duties, known as organizational citizenship behavior, is essential for maintaining service quality and organizational effectiveness, especially in the hospitality industry. Job satisfaction is a key factor influencing employees’ positive attitudes and willingness to engage in extra-role behaviors, while organizational commitment serves as a psychological attachment that fosters loyalty and enhanced contribution. This study aims to examine the effect of job satisfaction on OCB, both directly and through the mediation of organizational commitment. A causal-explanatory approach was employed, involving all 45 hotel employees as respondents using saturated sampling. Data were collected through questionnaires, and their validity and reliability were confirmed before analysis. Path analysis and the Sobel test were used to assess direct and mediated relationships among variables. The results indicate that job satisfaction positively affects OCB and significantly influences organizational commitment. Organizational commitment also contributes to OCB and mediates the relationship between job satisfaction and OCB. These findings highlight that enhancing employee satisfaction and commitment is a crucial strategy for fostering proactive behaviors and improving overall organizational performance.